PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, DAN SIZE TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode Tahun 2012-2015) - Yusva Pradipta, 11.05.52.0017; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2016)
This study aims to determine the effect of profitability, liquidity, leverage, and the size of the dividend payout ratio for companies listed in Indonesia Stock Exchange year period 2012-2015. This study uses secondary data obtained from the financial statements www.idx.co.id. The population in this study are all manufacturing companies went public and its shares are listed on the Indonesia Stock Exchange (BEI). Samples were selected using purposive sampling technique. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that the positive effect on the profitability of the dividend policy, meaning that the higher profitability of the higher the dividend. Liquidity has no effect on dividend policy. Leverage does not affect the dividend policy. Size does not affect the companys dividend policy.Â Â Keywords: Profitability, Liquidity, Leverage, Size, Dividend Payout Ratio